Effectiveness of English Textbooks of Oxford University Press according to Teachers' and Students' Perspectives. - Imran, Abida; Batool, Filza; Altaf, Faiza; Lodhi, Muhammad Arfan (Bulletin of Advanced English Studies (BAES), 2024)
Objectives: The current study is an attempt to examine the effectiveness of English textbook published by Oxford University Press and being taught to the students of grade 5 in many private schools. During last few years, government of Pakistan has implemented the concept of Single National Curriculum (SNC) to get it introduce and functional in every educational institution of the country. For this purpose, state-owned and private publishers brought modifications in their curricula and materials in order to ensure their alignment with the SNC. Methods: Researcher adopted descriptive framework in this survey-based research to gather and analyze the data quantitatively. The randomly selected 200 teachers and 100 students with equal proportion of gender was determined as the sample of the study. Two different types of questionnaires were taken as data collection tools in order to obtain information from the participants. Findings: The obtained results indicated diversity of findings regarding effectiveness and utilization of Oxford English textbooks in schools. The participants highlighted the importance of textbooks, its impressive content, logical organization, comprehensive exercises, and meticulous course learning objectives. However, it was also found that textbook is expensive, lack cultural components, ignore real life linguistic issues, and devoid of maintaining learning and teaching interest. It was also found that teachers are not given proper trainings on implementing textbook-based instructional strategies in English classrooms. Research implications: The problems and challenges highlighted by students and teachers may benefit the school administrators, implementers and managers to devise their further policies, which may facilitate learning effectively.